Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/15299716.2018.1485071
|View full text |Cite
|
Sign up to set email alerts
|

‘Femme it Up or Dress it Down’: Appearance and Bisexual Women in Monogamous Relationships

Abstract: This paper reports on findings from a qualitative study into the lived experience of bisexual women in monogamous relationships. Nineteen selfidentified bisexual women from across the UK, who were either in a monogamous relationship or desired to be in one, were explored. Participants completed diaries and took part in telephone interviews. The data was analysed using Template Analysis (King, 2004) which identified themes from the data set. It appeared that women in different-gender relationships choose appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…As a result, participants suggested that interpreting plurisexuality was done by ‘spotting people who are doing their gender a bit wrong’ (Jessie, 44, bisexual, female/genderqueer/enby). The way in which participants described this process fell in line with Daly et al’s (2018) suggestion of bisexual women adopting a chameleon-like presentation which communicated femininity and masculinity simultaneously or being serially dependent on context. However, some participants decidedly leaned into visions of masculinity or femininity to communicate their sexual identities.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…As a result, participants suggested that interpreting plurisexuality was done by ‘spotting people who are doing their gender a bit wrong’ (Jessie, 44, bisexual, female/genderqueer/enby). The way in which participants described this process fell in line with Daly et al’s (2018) suggestion of bisexual women adopting a chameleon-like presentation which communicated femininity and masculinity simultaneously or being serially dependent on context. However, some participants decidedly leaned into visions of masculinity or femininity to communicate their sexual identities.…”
Section: Resultsmentioning
confidence: 66%
“…In these ways, plurisexuals are operating from a space of invisibility. Many plurisexuals -in this study and others -have expressed their desire to be visible (Daly et al, 2018;Hartman, 2013;Hartman-Linck, 2014;Lynch and Maree, 2017). It is important to question what visibility may mean here.…”
Section: Plurisexuality Visibility and Gendermentioning
confidence: 78%
See 3 more Smart Citations